THREE-DIMENSIONAL INTEGRATED CIRCUIT FOR ANALYTE DETECTION - BARNETT, BRANDON; RAMANATHAN, SHRIRAM; DATTA, SUMAN; KAVALIEROS, JACK T; BRASK, JUSTIN K (2008)
The embodiments of the invention relate to a device having a first substrate comprising a transistor; a second substrate; an insulating layer in between and adjoining the first and second substrates; and an opening within the second substrate, the opening being aligned with the transistor; wherein the transistor is configured to detect an electrical charge change within the opening. Other embodiments relate to a method including providing a substrate comprising a first part, a second part, and an insulating layer in between and adjoining the first and second parts; fabricating a transistor on the first part; and fabricating an opening within the second part, the opening being aligned with the transistor; wherein the transistor is configured to detect an electrical charge change within the opening. L'invention concerne un dispositif dont un premier substrat comporte un transistor ; un second substrat ; une couche d'isolation placée entre les deux substrats et attenante au premier et second substrat ; et une ouverture pratiquée dans le second substrat et alignée avec le transistor, lequel est conçu pour détecter un changement de charge électrique dans l'ouverture. L'invention concerne également un procédé comprenant la fourniture d'un substrat pourvu d'une première partie, d'une seconde partie et d'une couche d'isolation située entre les deux parties et attenante à la première et à la seconde partie ; la fabrication d'un transistor sur la première partie ; et la fabrication d'une ouverture dans la seconde partie, l'ouverture étant alignée avec le transistor. Le transistor est conçu pour détecter un changement de charge électrique dans l'ouverture.